2021
DOI: 10.1038/s41467-021-21400-3
|View full text |Cite
|
Sign up to set email alerts
|

Coupled nitrification and N2 gas production as a cryptic process in oxic riverbeds

Abstract: The coupling between nitrification and N2 gas production to recycle ammonia back to the atmosphere is a key step in the nitrogen cycle that has been researched widely. An assumption for such research is that the products of nitrification (nitrite or nitrate) mix freely in the environment before reduction to N2 gas. Here we show, in oxic riverbeds, that the pattern of N2 gas production from ammonia deviates by ~3- to 16-fold from that predicted for denitrification or anammox involving nitrite or nitrate as free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…9). There was no significant difference observed between groups with and without adding allylthiourea (a nitrification inhibitor 66 ), indicating that N 2 O production via hydroxylamine oxidation was minimal under in situ conditions. By contrast, nitrifier denitrification was likely a potential contributor in the plastisphere and bulk water (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 96%
“…9). There was no significant difference observed between groups with and without adding allylthiourea (a nitrification inhibitor 66 ), indicating that N 2 O production via hydroxylamine oxidation was minimal under in situ conditions. By contrast, nitrifier denitrification was likely a potential contributor in the plastisphere and bulk water (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 96%
“…There are 65 Tg N 2 difference to make the balance for N 2 geocycling. A recent survey on riverbed indicated that N 2 production from denitrification and anammox was lower than the measured N 2 production, and a cryptic source was contributed to N 2 production from ammonia oxidation ( 33 ). In a recent study, we found a previously unknown process, Dirammox, for aerobic ammonia oxidation, and hydroxylamine was the intermediate ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…They have previously shown strong dependence on organic carbon supply (Harder and Attwood, 1978;Condón et al, 1996;Surono et al, 2008), likely due to their aerobic reaction pathway catalyzed by cytochrome o oxidase (Ji et al, 2015). Often, nitrification and facultative denitrification are closely coupled in coastal sediments (Ouyang et al, 2021) while their reaction rates vary under different environmental settings (Calvo-Martin et al, 2021). Net NO 3 − production in our experiments (group A) reveals the dominance of nitrification, probably fed by organic matter ammonification with contributions from the adsorbed pool, while NO 3 − removal stimulated by addition likely results from both denitrification and NO 3 − assimilation under such aerobic environment (Jiang and Jiao, 2016), since Anammoxcapable microorganisms were not identified here.…”
Section: − Transformationsmentioning
confidence: 99%